PEREZ, Reginaldo Teixeira. O Pensamento Político de Roberto Campos: da razão do Estado à razão do mercado (1950-1995). 2ª Ed. Editora UFSM: Santa Maria, 2021. - Camfield Barbosa, Luis Guilherme; da Silva Vaccari, Gabriel (Conexão Política, 2023)
PEREZ, Reginaldo Teixeira. O Pensamento Político de Roberto Campos: da razão do Estado à razão do mercado (1950-1995). 2ª Ed. Editora UFSM: Santa Maria, 2021.